Uniformity or polarization?: The nuclear power debate in Japanese newspapers and political coalitions, 1973-2014 - Weiß, Tobias (Contemporary Japan, 2021)
The image of Japanese mainstream media reporting is dominated by the institution of “press clubs”. Critical researchers argue that these restricted and institutionalized links between mainstream media and their sources lead to uniformity in media reporting. Other researchers contend that Japanese journalists play diverse roles and frame issues in diverse ways. These contrasting theses are explored through an analysis of three major newspaper's framing of nuclear power in article series (rensai). First, we construct a set of frames of the nuclear power issue out of materials from two political alliances: the pronuclear alliance (the so called “nuclear village”), and the antinuclear alliance. We apply and adapt these frames using a sample of newspaper article series from 1973 to 2014. The comparison shows that there are significant differences of reporting both between newspaper organizations as well as between different periods. Especially for the phase after 2011, reporting turns pronouncedly nuclear-skeptical in two newspapers. While not denying press club influence, the analysis cautions against mechanically applying a distinction between “insider” and “outsider” media and calls for new analytical categories to explain the substantial differences of framing between journalists of various “insider” media organizations. (Contemp Jap / GIGA)
Keywords: Japan; Fukushima